The Role of Macrophages in the Infarcted Myocardium: Orchestrators of ECM Remodeling - O'Rourke, Sinead A.; Dunne, Aisling; Monaghan, Michael G. (Frontiers in Cardiovascular Medicine, 2019)
Myocardial infarction is the most common form of acute cardiac injury attributing to heart failure. While there have been significant advances in current therapies, mortality and morbidity remain high. Emphasis on inflammation and extracellular matrix remodelling as key pathological factors has brought to light new potential therapeutic targets including macrophages which are central players in the inflammatory response following myocardial infarction. Blood derived and tissue resident macrophages exhibit both a pro- and anti-inflammatory phenotype, essential for removing injured tissue and facilitating repair, respectively. Sustained activation of pro-inflammatory macrophages evokes extensive remodelling of cardiac tissue through secretion of matrix proteases and activation of myofibroblasts. As the heart continues to employ methods of remodelling and repair, a destructive cycle prevails ultimately leading to deterioration of cardiac function and heart failure. This review summarizes not only the traditionally accepted role of macrophages in the heart but also recent advances that have deepened our understanding and appreciation of this dynamic cell. We discuss the role of macrophages in normal and maladaptive matrix remodelling, as well as studies to date which have aimed to target the inflammatory response in combatting excessive matrix deposition and subsequent heart failure.